Appearance of Subchondral Bone in Computed Tomography Is Related to Cartilage Damage in Osteochondral Lesions of the Talar Dome. (June 2014) - Nakasa, Tomoyuki; Adachi, Nobuo; Kato, Tomohiro; Ochi, Mitsuo
Background: Osteochondral lesions of the talar dome (OLT) involve the articular cartilage and/or subchondral bone. The subchondral bone plate plays an important role in cartilage metabolism. We hypothesized that the findings of subchondral bone on CT image would be related to the cartilage damage of OLT. The purpose of this study was to evaluate the relationship between the arthroscopic and CT findings focused on subchondral bone. Methods: Thirty-one ankles diagnosed as OLT were analyzed. All patients underwent CT, MRI, and arthroscopic surgery. The CT findings for both the cystic and fragment lesions were classified into 3 types. The 3 types for the cystic lesion ankles were irregular shape, round shape with sclerotic wall, and irregular shape with opening to an articular cavity. The 3 types for the fragment lesion were no bone absorption, bed absorption without fragment absorption, and bed sclerosis and fragment absorption. The subchondral bone findings on CT were compared with International Cartilage Repair Society (ICRS) grades and arthroscopic grading. Results: All round and sclerotic cystic lesions revealed cartilaginous flap lesions with a nearly normal cartilage surface. An irregular shape with opening revealed an unstable lesion with severely damaged cartilage. As for fragment lesions, no absorption revealed a stable lesion with a nearly normal cartilage surface. Bed absorption revealed an unstable lesion with a nearly normal cartilage surface. Fragment absorption with bed sclerosis showed an unstable lesion with severely damaged cartilage. There was a significant difference between CT findings and ICRS grade or arthroscopic findings (both P < .01), while there was no significant difference with MRI grading. The diagnosis of cartilage status by CT was better than MRI. Conclusion: CT findings for OLT based on subchondral bone related to cartilage damage. This study showed that CT was a useful tool for evaluating cartilage damage in OLT. Level of Evidence: Level III, comparative case series.